Development of a Pediatric Physiologically Based Pharmacokinetic Model for Sirolimus: Applying Principles of Growth and Maturation in Neonates and Infants. (4th February 2015) - Emoto, C; Fukuda, T; Johnson, TN; Adams, DM; Vinks, AA
<x xml:space="preserve">Abstract</x> This study describes the maturation of sirolimus clearance in a cohort of very young pediatric patients with vascular anomalies. The relationship between allometrically scaled in vivo clearance and age was described by the Emax model in patients aged 1 month to 2 years. Consistent with the observed increase, in vitro intrinsic clearance of sirolimus using pediatric liver microsomes showed a similar age‐dependent increase. In children older than 2 years, allometrically scaled sirolimus clearance did not show further maturation. Simulated clearance estimates with a sirolimus physiologically based pharmacokinetic model that included CYP3A4/5/7 and CYP2C8 maturation profiles were in close agreement with observed in vivo clearance values. In addition, physiologically based pharmacokinetic model‐simulated sirolimus pharmacokinetic profiles predicted the actual observations well. These results demonstrate the utility of a physiologically based pharmacokinetic modeling approach for the prediction of the developmental trajectory of sirolimus metabolic activity and its effects on total body clearance in neonates and infants.